The Hypothesis Framework for the Relationship between Emotional Intelligence and Organizational Commitment and the Influence of Job Satisfaction as a Mediator - Zaid Mustafa, Mohamad; Buntat, Yahya; Rasid Abdul Razzaq, Abdul; Ahad, Rosnee (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to propose a hypothesized framework for the relationship between emotional intelligence and organizational commitment and the influence of job satisfaction as a mediator among technical teachers at the Ministry of Education, Vocational College of Malaysia. The detailed study that will be carried out in this study using the Strutural Equation Modeling (SEM) approach with AMOS 20 software will be used to validate the hypothesized framework developed. To this end, the hypothesis framework was developed using a meta-analysis approach from previous theories and studies. From these methods, constructs, sub-constructs, and sub-sub-constructs of the study are formed. From the analysis of the three research areas derived from emotional intelligence, job satisfaction, and organizational commitment, the sub-constructs for emotional intelligence are self-awareness, self-management, social awareness, and relationship management, while the sub-constructs for job satisfaction are salary, promotion, supervision, side benefits, operating conditions, co-workers, working conditions, and internal communications, and the sub-constructs for organizational commitment are affective commitment, continuance commitment, and normative commitment. The findings from the meta-analysis were distributed to 30 experts from the teachers of electrical and electronic engineering, civil engineering, and mechanical engineering from the Vocational College to determine the suitability of whether the constructs, subconstructs, and sub-subconstructs of the study were necessary or rather within the framework of the research hypothesis. Finally, from the validation of the 30 experts, there are 4 constructs, 10 subconstructs, and 15 sub-constructs that remain in the hypothesis framework of this study.